2017
DOI: 10.1136/vr.104142
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance imaging findings in epileptic cats with a normal interictal neurological examination: 188 cases

Abstract: Epilepsy is a common neurological condition in dogs and cats. Although an increased likelihood of significant brain lesions with age has been identified in neurologically normal dogs with epileptic seizures, the underlying aetiology of epileptic seizures in cats that present with normal physical and neurological examinations remains unknown. In this cross‐sectional study, the authors examined MRI findings in a large population of cats with a normal interictal physical and neurological examination. They hypothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 45 publications
1
20
0
Order By: Relevance
“…15 Acquired meningoencephaloceles are rarely described in cats and can be of non-traumatic, traumatic and spontaneous origin following the human classification scheme. 16,17 In the present case an iatrogenic traumatic aetiology was obvious.…”
Section: Discussionsupporting
confidence: 49%
“…15 Acquired meningoencephaloceles are rarely described in cats and can be of non-traumatic, traumatic and spontaneous origin following the human classification scheme. 16,17 In the present case an iatrogenic traumatic aetiology was obvious.…”
Section: Discussionsupporting
confidence: 49%
“…Raimondi et al recently reported that 23% of cats older than 6 years at seizure onset with a normal interictal neurologic examination had a significant structural abnormality on MRi causing their seizure disorder. 30 The most common causes of structural epilepsy in cats include neoplasia, inflamma-tory disorders, and vascular disorders such as infarcts or hemorrhage. 1,7,11,16,17,20 Congenital anomalies, degenerative disorders, storage diseases and thiamine deficiency have also been reported.…”
Section: Seizures Of Intracranial Originmentioning
confidence: 99%
“…The diagnosis of IE (primary epilepsy or unknown epilepsy) is one of exclusion and in dogs and cats is traditionally made based on typical signalment and seizure history, unremarkable interictal physical and neurologic examination, exclusion of under lying metabolic and toxic causes, and inability to find an intracranial cause (Table 2). 1,3,5,6,10,14,23,29,30,61,62 These criteria for diagnosis have been problematic in cats, however, because until recently the published reports describing cats with IE have been very limited. Historically, iE was considered to be an uncommon cause of seizures in cats.…”
Section: Idiopathic Epilepsymentioning
confidence: 99%
See 2 more Smart Citations